Synthesis, Mesomorphic, and Solar Energy Characterizations of New Non-Symmetrical Schiff Base Systems - Alamro, Fowzia S.; Ahmed, Hoda A.; Gomha, Sobhi M.; Shaban, Mohamed (Frontiers in Chemistry, 2021)
New asymmetrical Schiff base series based on lateral methoxy group in central core, (E)-3-methoxy-4-(((4-methoxyphenyl)imino)methyl)phenyl 4-alkoxybenzoate (An), were synthesized and investigated their optical and mesomorphic characteristics. The lateral OCH3 group is incorporated into the central benzene-ring in ortho position with respect to the azomethine linkage. Molecular structures were elucidated by elemental analyses, FT-IR and NMR spectroscopy. Characterization of their mesomorphic behaviours, were carried out using differential scanning calorimetry (DSC) and polarized optical microscopy (POM). Their examinations indicated that, all the designed series are monomorphic possessing nematic (N) mesophase enantiotropically except A12 derivative has exhibiting monotropic N phase. A comparative study was made between the present investigated series (An) and their corresponding isomers (Bn). The results revealed that, the kind and stability of the mesophase as well as its temperature range are affected by the location and special orientation of the lateral methoxy group. Also, the electric resistance, conductance, energy gap, and Urbach Energy were reported for the present investigated An series. Results revealed that, all electrodes exhibit Ohmic behaviors with electric resistances in the GΩ range, whereas the electric resistance was decreased from 221.04 GΩ to 44.83 GΩ by lengthen the terminal alkoxy-chain to n=12. The band gap of the An series was reduced from 3.43eV to 2.89 eV by increasing the terminal chain length from n=6 to n=12 carbons. Therefore, controlling the length of the terminal chain can be used to improve the An series' electric conductivity and optical absorption, making it suitable for solar energy applications.